PELAYANAN PUBLIK BERBASIS ONLINE DI DESA (STUDI PADA EMPAT DESA DI KECAMATAN JATINANGOR) - Ikhbaluddin, Ikhbaluddin (Jurnal Teknologi dan Komunikasi Pemerintahan, 2021)
Villages as one of the sub-systems of the government in Indonesia that carry out governance functions is at the forefront in providing services to the community. Especially, it is very essential in the midst of the current demands for easy, cheap, and fast services. One alternative solution to these demands is the use of information technology in the field of government (e-government), such as a website-based online service media. However, in reality, the villages that are used for this research location generally still provide services to the community in a conventional manner. Even when the websites are available, they do not meet the standards in e-government development. The method used in this research is qualitative with a descriptive approach, and with data collection techniques through interviews and observation. The study concludes that Cibeusi Village, Hegarmanah Village, Cileles Village, and Cilayung Village are still not optimal in utilizing website media as an alternative for online public services. Moreover, the necessary features related to online public services, namely information, interactions, and transactions are still not yet available. Keywords: Villages, Online Public Services